Dynamic Changes in the Systemic Inflammation Response Index Predict the Outcome of Resectable Gastric Cancer Patients - Liu, Zhenhua; Ge, Haijue; Miao, Zhilong; Shao, Shoupeng; Shi, Hongtai; Dong, Congsong (Frontiers in Oncology, 2021)
The systemic inflammation response index (SIRI) has been revealed to be closely related to the prognosis of a variety of tumours. Whether the dynamic change in SIRI before and after surgery can be used to judge the prognosis of patients after radical gastrectomy has not yet been studied. In this study, the predictive ability of preoperative SIRI and changes in SIRI before and after surgery for the survival rate of gastric cancer patients was evaluated in two independent cohorts. It was found that SIRI was closely related to TNM staging. The higher the TNM stage, the higher the proportion of patients with a high SIRI. However, SIRI was not related to any other clinicopathological parameters. Kaplan-Meier survival analysis showed that a high SIRI was associated with poor prognosis in gastric cancer patients in the original cohort and in the validation cohort. SIRI, NLR, PLR, and MLR could be used to judge the prognosis of patients with operable gastric cancer. However, multivariate analysis suggested that only SIRI was an independent prognostic factor for patients with operable gastric cancer. In addition, the change in SIRI at 4-6 weeks after surgery compared with SIRI before surgery was closely related to the survival of gastric cancer patients. Compared with the unchanged group (absolute variation <50%), gastric cancer patients with a SIRI increase >50% had a worse OS, while patients with a SIRI decrease >50% had a better prognosis. In conclusion, SIRI can be used as a reliable index to evaluate the prognosis of patients with operable gastric cancer, and the dynamic change in SIRI before and after surgery is significantly related to the prognosis of patients with gastric cancer.